Not Merely a Tourist Site: Jamaica Kincaid’s Evocation of Antigua in A Small Place - Hossain, Sanjeeda (Spectrum, 2025)
Jamaica Kincaid in her book A Small Place (1981) describes Antigua as a holiday destination. As she revisits her homeland after a long period, she adopts a postcolonial perspective in viewing the island’s contemporary socio-political system. Though the British colonizers and slave-traders have left, the colonial legacy persists with their heirs' continual arrival to the island as tourists. Meanwhile, Kincaid notes that the majority of Antiguans, who were descendants of former slaves, remain subjugated. The writer argues that the histories of slavery and colonialism are hindrances to Antigua’s formation of its identity as an independent and self-reliant state. This paper studies Kincaid’s narration from the perspective of a solo female traveller travelling back to her native land as a tourist. By doing so, it will examine the difficulties she confronts during her travel that affect her narrative. Spectrum, Volume 18, June 2023: 31-39